Energy in Newfoundland - Millan, Steven (Geoscience Canada, 1974)
Summary Energy requirements of the Province of Newfoundland are met almost entirely by hydroelectricity and petroleum fuels in the ratio of 1:4. Hydroelectric resources, both developed and potential, are very large in relation to the Province's requirements. The petroleum potential of the Province is also substantial and undergoing extensive exploration in the offshore Atlantic area. Two wells drilled in 1973, on the northern Grand Banks and on the Labrador shelf, seem particularly significant.